The Impact of Post-Operative Phrenic Nerve Dysfunction on Lung Function Parameters and Long-Term Outcomes After Lung Transplantation - Keita Nakanishi; Keita Nakanishi; Caroline Hillebrand; Thomas Schweiger; Stefan Schwarz; Shahrokh Taghavi; Peter Jaksch; Alberto Benazzo; Toyofumi Fengshi Chen-Yoshikawa; Konrad Hoetzenecker; Konrad Hoetzenecker (Transplant International)
A rare but important complication after lung transplantation (LTx) is postoperative phrenic nerve dysfunction (PND). Diaphragmatic plication (DP) is a well-established treatment option for PND, however, the long-term effect of PND and DP on lung function parameters and survival after LTx are currently unknown. We retrospectively reviewed 1400 LTx recipients transplanted at Medical University of Vienna between 01/2003 and 12/2022. Fluoroscopy and/or phrenic nerve conduction studies confirmed PND when chest radiographs after extubation showed a unilateral heightened diaphragm. We identified 25 patients with post-operative PND, of whom 12 underwent DP. The remaining 1,375 patients served as a control group. Median ICU-stay and hospital-stay were significantly longer in the PND groups (DP: 20 and 57 days; non-DP: 27 and 43 days; control group: 7 and 25 days; P = 0.001/P < 0.001). PND led to consistently lower %TLC in lung function tests performed within the first three years after LTx. DP was associated with lower %FEV1.0 early after LTx but it aligned to %FEV1.0 of the other groups during follow-up. Although PND significantly affected postoperative recovery after LTx, it did not impair long-term survival outcomes.